Heat, greed and human need : climate change, capitalism and sustainable wellbeing - Gough, Ian.; Edward Elgar Publishing (Edward Elgar Pub., 2017)
This exceptional book considers how far catastrophic global warming can be averted in an economic system that is greedy for growth, without worsening deprivation and inequality. The satisfaction of human needs - as opposed to wants - is the only viable measure for negotiating trade-offs between climate change, capitalism and human wellbeing, now and in the future. The author critically examines the political economy of capitalism and offers a long-term, interdisciplinary analysis of the prospects for keeping the rise in global temperatures below two degrees, while also improving equity and social justice. A three-stage transition is proposed with useful practical policies. First, 'green growth': cut carbon emissions from production across the world. Second, 'recompose' patterns of consumption in the rich world, cutting high-energy luxuries in favour of low-energy routes to meeting basic needs. Third, because the first two are perilously insufficient, move towards an economy that flourishes without growth. Heat, Greed and Human Need is vital for researchers and students of the environment, public and social policy, economics, political theory and development studies. For those advocating political, social and environmental reform this book presents excellent practical eco-social policies to achieve both sustainable consumption and social justice.
Contents: Introduction -- 1. The social dimensions of climate change -- 2. Human needs and sustainable wellbeing -- 3. Climate capitalism: emissions, inequality, green growth 4. Sustainable wellbeing, necessary emissions and fair burdens -- 5. From welfare states to climate mitigation states? -- 6. Decarbonising the economy and its social consequences -- 7. Decarbonising consumption: Needs, necessities and eco-social policies -- 8. Post-growth, redistribution and wellbeing -- 9. Conclusion: a three-stage transition -- Index.
Includes index.
Description based on print record.
Keywords: Climate change mitigation -- Economic aspects; Capitalism; Sustainable development; Electronic books